Multi-loop controller design for a heat exchanger - Wellenreuther, Andrea; Gambier, Adrián; Badreddin, Essameddin (IEEE International Symposium on Computer-Aided Control Systems Design, 2006, 2006)
A new method to tune the parameters of two discrete controllers in a cascaded control structure is proposed and applied to the linear controller design of a heat exchanger system. Normally, this problem is solved either by decoupling the multiple loops and tuning the controllers independently or by keeping the structure but tuning the controllers consecutively from inwards to outwards. However, these methods are not always an appropriate solution. Therefore, this approach that is derivated from the game theory is applied in this paper for a heat exchanger system where discrete controllers of two cascaded loops act as players in a cooperative game. The players operate simultaneously and influence themselves. Each player has its own objective function, which also depends on parameters of the other players. Target of the game is to get values for the parameters, satisfying the objective functions of the players, which is done via multi-objective optimization.
Gesehen am 11.12.2019